CHROMEBOOK INTEGRATION IN ISLAMIC RELIGIOUS EDUCATION LEARNING TO STRENGTHEN STUDENTS' DIGITAL LITERACY AND RELIGIOUS CHARACTER - Mochamad Galih Dikapusti Gunawan; Devi Sulaeman; Mia Audina Musyadad; Agus Agus; Asep Supriatna (Indonesian Journal of Islamic Studies (IJIS), 2026)
The development of digital technology in education demands the integration of learning tools that not only enhance cognitive competence but also shape students' character. In the context of Islamic Religious Education, the use of digital devices needs to be directed to align with the strengthening of digital literacy and religious values. This study aims to analyze the integration of Chromebooks in Islamic Religious Education learning and its contribution to strengthening digital literacy and the religious character of students at Marga Mulya II Elementary School, North Bekasi. The study used a qualitative approach with a case study. Data were collected through participant observation, in-depth interviews, and documentation studies. Then, they were analyzed using an interactive model that included data reduction, data presentation, and conclusion drawing. The results show that Chromebook integration was implemented in a structured manner through digital-based learning planning, interactive activities, and controlled online evaluation. Students' digital literacy developed through the habit of using devices in an orderly and responsible manner. At the same time, religious character traits such as honesty, discipline, and responsibility were internalized through the association of technology use with religious values. These findings confirm that technology can be a medium for developing digital competency and character when managed through appropriate pedagogical design. This research has implications for the importance of developing technology-based, integrative, and values-oriented Islamic Religious Education learning models in elementary schools.